2024
DOI: 10.1037/cpp0000474
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and coping strategies in pediatric and neonatal intensive care staff.

Abstract: Objective: Staff in pediatric and neonatal intensive care units (PICU and NICU) experience high rates of burnout due to the highly stressful environment. There is growing literature describing stress and burnout, but to date, no review of the evidence specific to pediatric and neonatal intensive care. For the development of interventions to reduce and prevent burnout, there needs to be a better understanding of this evidence. Little is known about coping strategies employed by critical care staff; it is import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…Despite this, there is very little work investigating successful coping strategies or interventions designed to improve workplace wellbeing. 28 This is a grave problem requiring urgent attention. 18,19,29 Indeed, recent research with interdisciplinary health care professionals, parents and families found that parties identified PCC staff well-being as a key priority.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, there is very little work investigating successful coping strategies or interventions designed to improve workplace wellbeing. 28 This is a grave problem requiring urgent attention. 18,19,29 Indeed, recent research with interdisciplinary health care professionals, parents and families found that parties identified PCC staff well-being as a key priority.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, there is very little work investigating successful coping strategies or interventions designed to improve workplace well‐being 28 . This is a grave problem requiring urgent attention 18,19,29 .…”
Section: Introductionmentioning
confidence: 99%
“… 13 A recent review which examined levels of burn-out and coping mechanisms employed by staff in paediatric and neonatal intensive care confirmed levels of burn-out were high, but the coping strategies used were not found to be effective. 14 This demonstrates a need for more effective mechanisms to improve well-being and increased self-awareness to enable staff to recognise what works for them. We know that burn-out, stress and psychological distress experienced by PCC staff can lead to them leaving the profession.…”
Section: Introductionmentioning
confidence: 99%
“…To date, research has focused on measuring the extent of the problem, but Butcher et al ’s 2023 review 14 and the small amount of qualitative research undertaken to explore workforce well-being in PCC to date 8 16–18 have shown us that further work is required to fully grasp the nature of staff experiences within the context of their lifeworld—their lived experience. 19 To do this, we need to examine in-depth how individuals make sense of what constitutes well-being to them, to understand how they experience challenges to their well-being and how they might be able to integrate well-being strategies into their everyday lives to build resilience at work.…”
Section: Introductionmentioning
confidence: 99%